2002
DOI: 10.1046/j.1524-4741.2002.08306.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Toxicity Associated with Concurrent Adjuvant Radiation Therapy and Paclitaxel in Primary Breast Cancer Therapy

Abstract: The purpose of this study was to describe the toxicity of concurrent standard dose adjuvant radiation therapy (RT) and paclitaxel in a series of patients receiving primary breast cancer therapy. From June 1998 to April 1999, 20 patients with breast cancer received concurrent adjuvant radiation and paclitaxel. There were 16 patients (80%) with American Joint Committee on Cancer (AJCC) stage II disease and 4 with stage III disease. Eighteen patients, 12 postmastectomy and 6 breast conservation, were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 13 publications
2
55
0
1
Order By: Relevance
“…The severity of lung fibrosis did not differ significantly among the test groups either. Although some clinical trials reported an increased incidence of pneumonitis and esophagitis following combined PTX therapy with radiation (Taghian et al, 2001;Hanna et al, 2002;Chen and Okunieff, 2004), others reported no influence on the incidence of such adverse effects (Ellerbroek et al, 2003;Yu et al, 2003). Several clinical trials and in vivo experiments have discussed the subject, however, no definitive conclusion has been arrived at Choy et al, 1998;Yu et al, 2004;Kao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severity of lung fibrosis did not differ significantly among the test groups either. Although some clinical trials reported an increased incidence of pneumonitis and esophagitis following combined PTX therapy with radiation (Taghian et al, 2001;Hanna et al, 2002;Chen and Okunieff, 2004), others reported no influence on the incidence of such adverse effects (Ellerbroek et al, 2003;Yu et al, 2003). Several clinical trials and in vivo experiments have discussed the subject, however, no definitive conclusion has been arrived at Choy et al, 1998;Yu et al, 2004;Kao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Lung toxicities often result in lung fibrosis, necessitating change of the treatment method and causing much distress or even death of the patients (Penney and Rubin, 1977;Early Breast Cancer Trialists' Collaborative Group, 2000;Lind et al, 2002). Some clinical trials actually reported an increased incidence of pneumonitis following combined PTX therapy with radiation in patients with breast or lung cancer (Taghian et al, 2001;Hanna et al, 2002;Chen and Okunieff, 2004).…”
mentioning
confidence: 99%
“…Paclitaxel-induced interstitial pneumonia occurs in approximately 1% of treated patients (5,6). Although many of these side effects appear to be schedule and dose dependant (7,8), several reports have indicated that pulmonary toxicity is not in this category, and that paclitaxel may trigger pulmonary allergic responses (8)(9)(10)(11) (6,(12)(13)(14)(15) …”
Section: F I G U R E 2 Di F F U S E a L V E O L A R D A Ma G E A:mentioning
confidence: 99%
“…91,92 Tamoxifen and various chemotherapy agents have been associated with increased pulmonary side effects with PMRT. [93][94][95][96] Among 1624 women treated with radiotherapy to the breast or chest wall alone or locoregional radiotherapy to the breast or chest wall plus lymph nodes, pneumonitis developed in 3% of patients treated with locoregional radiotherapy and chemotherapy compared with 0.5% in all other patients (p = 0.0001) (level V evidence). 91 Radiation pneumonitis occurred in 8.8% of patients receiving concurrent locoregional radiotherapy and chemotherapy, as compared with 1.3% of patients receiving sequential treatment (p = 0.002).…”
Section: Pulmonary Toxicitiesmentioning
confidence: 99%
“…103 Several retrospective series have implicated the anthracyclines and taxanes as drugs associated with increased risks of toxicities to normal structures, including the skin, soft tissues, lung and heart, when delivered concurrently with radiotherapy (level V evidence). 46,93,94 The optimal sequencing of PMRT and adjuvant endocrine therapy is also unclear. A retrospective analysis of 84 postmenopausal women treated in the prospective randomized Danish study suggested a higher risk of pulmonary fibrosis among women who received concurrent tamoxifen and PMRT than among women who did not receive tamoxifen (OR 2.9, p = 0.007) (level V evidence).…”
Section: Sequencing Of Radiotherapy and Systemic Therapymentioning
confidence: 99%